Perancangan Aplikasi Sistem Monitoring Kondisi Lalu Lintas Berbasis Android - Hadi Anwarsyah; Muhammad Farid Firdaus; Aninda Agustin Nurfajrina; Sofyan Mufti Prasetiyo (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Traffic congestion is undoubtedly one of the most common problems in big cities, and one of them is the city of Bandung. The inherent effects of congestion include delays for road users, wasted energy, possibly increased air pollution, increased stress on road users, disrupted the smooth operation of emergency vehicles such as ambulances and fire engines. There are several factors that cause traffic jams, such as traffic jams and bad weather. Sometimes the weather cooperates Every place is different even though they are still in the same city. This is an unpredictable situation for road users, so road users are not prepared for this condition. "SIKOMOLINTAS Android-Based Traffic Condition Monitoring System Application Design" is expected to be able to monitor vehicle users and provide information in the form of traffic density values, weather (temperature, humidity, rain status, and brightness) at any location where the system is located. This is part of a larger system, namely the Traffic Control and Monitoring System (SIKOMOLINTAS). The results achieved with this design are that the monitoring system can provide up-to-date information on traffic conditions based on actual conditions based on Android and can be integrated into SIKOMOLINTAS.